XPM-induced modulation instability in silicon-on-insulator nano-waveguides and the impact of nonlinear losses. (19th June 2018) - Chaturvedi, Deepa; Kumar, Ajit; Mishra, Akhilesh Kumar
Abstract: We have carried out an extensive theoretical study of cross-phase modulation induced modulation instability (MI) in a silicon-on-insulator nano-waveguide for two co-propagating waves. The analysis has been performed for two sets (with zero and varying non-zero walk-off parameter) of three different cases: when the two waves are in (i) normal dispersion regime, (ii) anomalous dispersion regime, and (iii) different dispersion regimes. In particularly, we have discussed the nonlinear losses due to two-photon absorption and free-carrier absorption. Further, we have investigated the impact of the walk-off parameter on the MI gain spectrum in the above three cases.